Sources of TFP growth in the Malaysian Islamic banking sector - Sufian, Fadzlan (Routledge, Taylor and Francis Group, 2009)
This paper attempts to empirically analyse productivity changes of the Malaysian Islamic banking sector during the period of 2001–2004 by applying the nonparametric Malmquist productivity index method. During the period of study, the empirical findings suggest that the Malaysian Islamic banking sector has exhibited productivity progress during the earlier years before declining during the latter years. The results suggest that foreign banks have exhibited higher productivity levels compared with their domestic counterparts during the earlier years, while the domestic banks’ productivity levels were relatively higher compared with the foreign banks during the latter years.